Derivatization and combination therapy of current COVID-19 therapeutic agents: a review of mechanistic pathways, adverse effects, and binding sites (2020)
Current treatment of patients with coronavirus 2019 (COVID-19) involves repurposed drugs that inhibit viral infection by either binding to their respective targets or via modulating cellular signal transduction. However, there is still a great deal of efficacy enhancement through combination therapy and derivatization. Combination therapy should involve agents with significant activity and different mechanisms of action. The structural map of the interaction between a drug and its target protein will help guide drug discovery for devising safe and effective ways to treat COVID-19. Herein, we report numerous synthetic designs based on enhanced affinity to the viral carbohydrate-rich protein spikes and proteinbinding sites of COVID-19.